A qualitative study on the effects of internet memes on university students' perception of news - Lee, Shau Yan (2020)
This study is conducted to examine the effects of internet memes on university students’ perception of news in Malaysia. Internet memes are the rising stars among variety of internet contents, and these are particular important element of communication especially among the younger internet users in their 20’s to 30’s. Digital study is an important academic sector as the world is now moving forward with daily advancement of technology. Malaysia as a developing country need to pick up its pace to research about local digital culture. Two research questions were set, what are the effects of internet memes on university students’ perception of news and are memes a reliable news source. The literature review discussed about the basic of internet memes, memes and news and media representation theory. The study conducted with qualitative interview of nine Malaysia’s university students. Interviews were recorded for transcriptions and then analysed and coded with the aid of NVivo12. The result concluded the effects of internet memes as products of short attention span, making issues entertaining and influencing perception. Memes was also concluded as not reliable news source.